Kebijakan Peningkatan Aksesibilitas Data Publik Sebagai Wujud Transparansi Pemerintah Kota Medan - Danny Pratomo (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2026)
Public information disclosure is a fundamental prerequisite for achieving transparent and accountable governance. However, the implementation of open data in Medan City continues to face significant challenges due to the absence of an integrated data access system linking village (kelurahan) administrations and local government agencies. This condition has reduced governmental transparency, limited public participation, and weakened the effectiveness of evidence-based decision-making. This study aims to identify the main challenges and formulate policy recommendations to improve public data accessibility. The research employs a descriptive qualitative approach using the Urgency, Seriousness, and Growth (USG) analysis method. The findings reveal that the primary issue is the absence of an integrated open data portal, which is driven by the local government's limited commitment, inadequate human resource capacity, and the lack of standardized data management. Therefore, this study recommends the enactment of a Mayoral Regulation on public data governance to establish an integrated, transparent, and accountable data system that supports bureaucratic reform and enhances the quality of public service delivery.